Wat beteken "die Bybel sê"? "n Tipologie van leserskonstrukte - Smith, D. J. (Hervormde teologiese studies, 1991)
What does ‘the Bible says’ mean? A typology of reader constructs It is argued that the unity of the Bible, so important to (Reformed) theology, ethics and life, is inevitably the result of constructs on the part of reader communities. A typology of such constructs is suggested, organising of ‘the Bible’ in diverse ways, in order to facilitate discussion between systematic theologians and biblical scholars.